Pemilihan Jenis Obat Terbaik Untuk Gejala Batuk Remaja dengan Menggunakan Metode AHP dan ARAS - Kraugusteeliana Kraugusteeliana; Ahmad Subagiyo; Fidi Setyawan (JURIKOM (Jurnal Riset Komputer), 2022)
Medicine is something that is still believed by many people around the world to cure various medical-related diseases. Drug is a substance used in establishing a diagnosis, preventing, reducing and also treating a disease. One type of medicine is cough medicine, there are types and kinds of cough medicine, such as cough medicine in the form of syrup or tablets. At this time there are various brands of cough medicine that are sold in pharmacies. To  make it easier  for  the  community  to make decisions, it is very necessary to implement the SPK process which aims to further assist the community in choosing cough medicines to be purchased using the AHP method and the ARAS method. This decision is of course determined by several criteria, including expiration, age. , dosage of use, price, and brand.